Glass-forming property of hydroxyectoine is the cause of its superior function as a desiccation protectant - Galinski, Erwin A.; Tanne, Christoph; Meffert, Andrea; Golovina, Elena A.; Hoekstra, Folkert A. (Frontiers in Microbiology, 2014)
We were able to demonstrate that hydroxyectoine, in contrast to ectoine, is a good glass-forming compound. Fourier transform infrared (FTIR) and spin label electron spin resonance (ESR) studies of dry ectoine and hydroxyectoine have shown that the superior glass-forming properties of hydroxyectoine result from stronger intermolecular H-bonds with the OH group of hydroxyectoine. Spin probe experiments have also shown that better molecular immobilization in dry hydroxyectoine provides better redox stability of the molecules embedded in this dry matrix. With a glass transition temperature of 87 0C (vs. 47 0C for ectoine) hydroxyectoine displays remarkable desiccation protection properties, on a par with sucrose and trehalose. This explains its accumulation in response to increased salinity and elevated temperature by halophiles such as Halomonas elongata and its successful application in “anhydrobiotic engineering” of both enzymes and whole cells.